Source size and temporal coherence requirements of coded aperture type x-ray phase contrast imaging systems - Munro, Peter R.T. (2010)
There is currently much interest in developing X-ray Phase Contrast Imaging (XPCI) systems which employ laboratory sources in order to deploy the technique in real world applications. The challenge faced by nearly all XPCI techniques is that of efficiently utilising the x-ray flux emitted by an x-ray tube which is polychromatic and possesses only partial spatial coherence. Techniques have, however, been developed which overcome these limitations. Such a technique, known as coded aperture XPCI, has been under development in our laboratories in recent years for application principally in medical imaging and security screening. In this paper we derive limitations imposed upon source polychromaticity and spatial extent by the coded aperture system. We also show that although other grating XPCI techniques employ a different physical principle, they satisfy design constraints similar to those of the coded aperture XPCI.